Spatial distribution of phlebotominae in Puerto Iguazú-Misiones, Argentina-Brazil-Paraguay border area - Santini, María Soledad (2013)
Fil: Santini, María Soledad. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.